Creating Dance in the Hatha Yoga Concept - Junloon, Nualravee; Charassri, Naraphong (Journal of Urban Culture Research, 2014)
This article explores the integration between yoga concepts and the art of dance. It aims to discuss the genesis of a dance performance inspired by Hatha Yoga and specifically its concept of balancing hot and cold power. The terms Hatha Yoga and the art of creative dance and other terms related to Hatha Yoga concepts are accordingly discussed. Six areas of inquiry were considered in this research project. They were: a survey of source documents, expert interviews, the standard criteria of Thai national artists, audience evaluations, student dance workshops, along with other media and online information. The resulting dance creation consists of four acts centered on the concept of balance between the hot and the cold power of Hatha Yoga. Its stylistics are an intercultural combination of Thai and Western contemporary dances and yoga with symbolic white and black costumes relating to coolness and warmness, which together reflect the main theme – the power of harmony. The outdoor venue and time of day was selected for its natural ambience, lighting and sounds conducive to relaxation and congruent with the aims of Hatha Yoga.